Studi Karakteristik Fondasi Pelat Tipis Dengan Pengaku Tiang “+” Pada Tanah Granuler Melalui Uji Eksperimen Dan Analisis Pemodelan Menggunakan Software Abaqus - Syarif, Firman; Adi, Agus Darmawan; Saputra, Ashar (JURNAL SAINTIS, 2017)
[EN] The amount of damage that happened in Indonesian road is the impact of high traffic load exceeds the carrying capacity of the pavement. To reduce the problems that occur on the pavement the good systems of pavement are built, various studies conducted to produce a creative innovation in order to evaluate and improve the performance of the pavement system. this study has developed a new system of foundation with pile "+" to make the connection between plate and minipile (joint) becomes better. In this study, three models of foundation will be tested by loading test (following ASTM D 114 381 and ASTM D 3689 Pile Under static axial compressive load) to observe and analyze the behavior of the foundation model by loading centric and eccentric. In addition to laboratory tests this research also modeling analysis with Abaqus software to observe and analyze the behavior of the foundation model in terms of deformation and settlement. The results showed the distances between pile and pile provides a significant contribution in reducing the settlement in the foundation when given a maximum load of 20 kN, where is the foundation 1 had short distance between the other foundation the deformation and settlement is the smallest. The length of pile also give significant contribution to reduce the settlement like in foundation 3 that have 20 cm length of the pile have settlement and deformatioan smaller than the foundation 2 that have 10 cm length of the pile